Financial Accounting - Spiceland J.David (Mc Graw Hill, 2008)
David Spiceland, Wayne Thomas and Don Herrmann have developed a unique text based on over 50 collective years of experience in the classroom. They’ve brought together best practices like highlighting Common Mistakes, offering frequent Let’s Review exercises, integrating the course with a running Continuing Problem, demonstrating the relevance of the course to non-majors with a Career Corner, and communicating it all in a student-friendly Conversational Writing Style.